Obesity, diabetes and the cluster of the metabolic syndrome - Wilson, Peter (Henry Stewart Talks, 2007)
The effect of diabetes, obesity and overweight on risks for heart disease, Framingham Heart Study analyses, The effects in men and women, Metabolic studies of new diabetes, Population studies, Metabolic risk factor abnormalities generally precede the development of type 2 diabetes mellitus and contribute to the development of diabetes mellitus and accelerated atherosclerosis, Differences in lipids and triglycerides, Prevalence of the syndrome rises with age: increased risk of diabetes mellitus, subclinical vascular disease and clinical cardiovascular disease, Risk for the development of vascular disease, The European DECODE study, The AFCAPS study, Presence of the metabolic syndrome and increased levels of the inflammatory marker CRP may help to identify persons at higher risk of type 2 diabetes or vascular disease
Archived at 2021/02/25